An antigen detection enzyme immunoassay for the diagnosis of Rhodesiense sleeping sickness - Nantulya, V.M. (Wiley, 1989)
Summary A monoclonal antibody raised against a non–variable surface antigen of Trypanosoma brucei rhodesiense procyclic trypomastigotes was used to develop an antigen detection enzyme immunoassay for the diagnosis of rhodesiense sleeping sickness. The assay was evaluated using 211 sera from clinically suspected cases: 142 from parasitologically proven cases and 69 from patients who were negative on parasitological examination. The test was positive in 128 out of 142 parasitologically proven cases. The negative cases may have been in the early stages of the disease, or may represent patients with antibody levels sufficient to prevent detection of antigen. Of particular significance, however, was the finding that eight of the 69 patients with undiagnosed disease were antigen positive despite the negative parasitological findings. Since false–positive reactions were not observed with blood donor sera, or with sera from malaria, schistosomiasis and leishmaniasis patients, it is reasonable to conclude that the eight antigen–positive patients were actual cases of sleeping sickness. The remaining 61 cases who were negative for both parasitaemia and antigenaemia may conceivably represent the variety of diseases whose clinical manifestations resemble those of rhodesiense sleeping sickness. The antigen detection method would thus not only be complementary to parasitological diagnosis, but essential for correct diagnosis in certain stages of the disease.